Étude descriptive des effets secondaires de la chimiothérapie dans le cancer bronchopulmonaire non à petites cellules au niveau de l’unité d’oncologie du service de pneumologie du chu de Sétif - BOUZOURINE , Nardjes; CHETTAH , Chahinez; CHERRID , Oualid; SIDI SALAH , Warda Naima; GHOUL , Ibtissem ( Encadrant ) (Université Sétif1 Ferhat Abbas. Faculté de Médecine., 2023)
Bronchial or lung cancer is a major public health issue worldwide in terms of incidence and mortality in both men and women. The diagnosis of the disease remains challenging for both sexes. The objective of our series of studies is to evaluate the profiles of patients with non-small cell lung cancer (NSCLC) undergoing chemotherapy treatment in order to detect the adverse effects of these drugs. This is a retrospective descriptive study focusing on the prevalence of side effects related to anticancer agents. The study was conducted at the oncology unit of the pulmonary department and included 34 patients of both sexes over a period of 2 months, from February 1 to March 31, 2023. The average age was 65 years, with a male predominance and a sex ratio of 5.8. Most of the patients came from urban areas (71%). Active smoking was present in 61.67% of cases. Hypertension and diabetes were the main medical history with respective percentages of 17% and 15%. 67.64% of cases discovered their disease due to clinical symptoms, with the most common symptoms being cough (38%) and fatigue (26%). The most frequent histological type was adenocarcinoma in 67.64% of cases, with the most found metastatic sites being bone (36%) and pleura (23%). 50% of cases had a single metastatic site. The most commonly used chemotherapy protocols were PEMETREXED+CARBO (23%), PEMETREXED alone (20%), DOCETAXEL, and GEMZAR+CARBO in 9% of cases. The most commonly reported common side effects in patients were fatigue, nausea and vomiting, alopecia, and anemia. Our study was in accordance with the majority of previous studies, and the lack of correspondence found in our results could be related to the population size (34 patients), which seemed small compared to other studies.
Keywords: Cancer bronchique non à petites cellules; Chimiothérapie; effets secondaires; Nausée